1999
DOI: 10.1007/s100960050365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mec A fem B Duplex Polymerase Chain Reaction for Detection of Methicillin-Resistant Staphylococcus aureus

Abstract: This study systematically evaluated a recently described duplex polymerase chain reaction test for methicillin-resistant Staphylococcus aureus with 25 different German epidemic strains of methicillin-resistant Staphylococcus aureus and 66 staphylococci other than methicillin-resistant Staphylococcus aureus, including 17 different coagulase-negative staphylococcal species and subspecies, that were either oxacillin susceptible or oxacillin resistant. The results were compared with those of conventional cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…That ability has revealed PCR as a powerful tool in clinical microbiology studies (Cockerill, 1999). Several authors have already shown the feasibility of the PCR methodology for the identification of S. aureus strains and for the detection of antibiotic resistance genes (Cockerill, 1999;Jonas et al, 1999). We concluded that the procedure still require a minimum of 2 days before final results can be obtained, but these media proved to the more sensitive and specific than other media.…”
Section: Detection Of Meca Gene By Pcrmentioning
confidence: 82%
See 1 more Smart Citation
“…That ability has revealed PCR as a powerful tool in clinical microbiology studies (Cockerill, 1999). Several authors have already shown the feasibility of the PCR methodology for the identification of S. aureus strains and for the detection of antibiotic resistance genes (Cockerill, 1999;Jonas et al, 1999). We concluded that the procedure still require a minimum of 2 days before final results can be obtained, but these media proved to the more sensitive and specific than other media.…”
Section: Detection Of Meca Gene By Pcrmentioning
confidence: 82%
“…Mechanisms of methicillin resistant in S. aureus is based on the production of an additional low affinity penicillin binding protein (PBP; PBP2a), which is encoded by the mecA gene (Chambers., 1997). Accurate and quick identification of Methicillin Resistant Staphylococcus aureus (MRSA) in clinical specimen is essential for timely decision on isolation procedures and effective antimicrobial chemotherapy (Jonas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The femB gene codes for an enzyme important in cross-linking peptidoglycan in various different Staphylococcus spp. The specificity of the femB PCR primers used for DNA amplification of the species S. aureus has been demonstrated previously (8).…”
mentioning
confidence: 94%
“…Duplex PCR for mecA and femB provides reliable and unequivocal results for MRSA identification within 18 h (16). The specificity of the femB primers used for identification of S. aureus has been demonstrated previously (8). The potential coamplification of femB and mecA from mixed cultures consisting of R-CNS and MSSA is a theoretical weakness inherent in this method, as it would mimic a false-positive MRSA result (Vandenbroucke-Grauls and Kusters, letter).…”
mentioning
confidence: 95%
“…For these reasons, it has become important to develop rapid diagnostic tests to monitor the clinical utility of fluoroquinolones and also to minimize the emergence of resistance. Many molecularly-based tests have been recently developed to identify S. aureus and to determine its susceptibility to various antibiotics (10,11,17,22). While all these tests detected the presence of a specific gene to establish the antibiotic susceptibility profile, mutations in the targets of fluoroquinolones must be detected to determine the susceptibility to this class of antibiotics.…”
Section: Discussionmentioning
confidence: 99%